Business Analysis and Vegetable Hydroponic Marketing - Harahap, Gustami; Hernosa, Siswa Panjang; Lubis, Mitra Musika; Permatasari, Ella (Jurnal AGRISEP, 2024)
The purpose of this research is 1) To find out how much income hydroponic spinach farming is in Percut Sei Tuan District; 2) To determine the feasibility of hydroponic spinach farming in Percut Sei Tuan District; 3) To find out the marketing efficiency of hydroponic spinach farming in Percut Sei Tuan District. This research was conducted in Percut Sei Tuan District, Deli Serdang Regency, in December 2022. With a sample of 23 respondents, 8 owned hydroponic businesses, three collectors, five wholesalers, and seven consumers. The data used are primary data from interviews with questionnaires to find the 1st objective by the R/C ratio business feasibility analysis; the share margin analyzed for the 3rd objective. Based on the research, the results obtained: 1) the average income of hydroponic spinach vegetable farmers is IDR. 13,393,328 per planting period with an average land area of 294.50; 2) Farming is feasible with R/C Ratio >1, which is 3.08, Volume BEP Value = 347,98 kg, BEP price value = IDR 8,237, Payback Period (PP) value = 0,33; 3) the three marketing channels are considered efficient, where the efficiency value is < 50%. Channel I is worth 1,47%, Channel II is 1,51%, and Channel III is 1,1%.